2004
DOI: 10.1002/mrc.1360
|View full text |Cite
|
Sign up to set email alerts
|

Combined ab initio computational and experimental multinuclear solid‐state magnetic resonance study of phenylphosphonic acid

Abstract: 1H, 13C, 17O and 31P NMR parameters, including chemical shift tensors and quadrupolar parameters for 17O, were calculated for phenylphosphonic acid, C6H5PO(OH)2, under periodic boundary conditions. The results are in very good agreement with experimental data and permit the unambiguous assignment of all the sites present in the structure. In particular, the 17O NMR parameters of the P=O and P-OH environments were precisely determined, which should help in the characterization of the bonding mode of phosphonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 39 publications
(31 reference statements)
7
92
0
Order By: Relevance
“…[4] The results of the calculation are in good agreement with the experimental data and permit the unambiguous assignment of all the sites present in the structure.…”
Section: Introductionsupporting
confidence: 70%
“…[4] The results of the calculation are in good agreement with the experimental data and permit the unambiguous assignment of all the sites present in the structure.…”
Section: Introductionsupporting
confidence: 70%
“…Multinuclear solid-state NMR spectroscopy was used to glean information about the environment of the phosphatic and citrate anions in the structure, which we then used to build a series of possible structural models. These models were geometry-optimized using first principles electronic structure calculations through the Cambridge Serial Total Energy Package (CASTEP) software (28)(29)(30) and the calculated NMR parameters and powder XRD patterns for the resulting optimized structures compared with experimental data to determine the plausibility of each structure (i.e., the degree to which the NMR parameters and powder XRD pattern calculated for a model structure agree with the experimental data). The true structure, because of its inherent disorder, is best described as the coexistence of a set of structures in this approach, and our ultimate goal here is to find a set of structures that defines the range of structural disorder within OCP-citrate.…”
Section: Resultsmentioning
confidence: 99%
“…only one geometry) are minimised, resulting in an expectation of increased accuracy from that point of view and throwing the burden of accuracy on the validity of the computations. Some CASTEP-NMR results for anisotropies have been reported for˛testosterone, 21 phenylphosphonic acid 30 and for several aminoacids. 31 In Table 5, we report the computed shielding parameters for the antibiotic ampicillin (VIII) and compare them with the experimental results of Antzutkin et al 42 The details of the computation are identical to those reported in Ref.…”
Section: Shielding Tensor Componentsmentioning
confidence: 95%
“…Indeed assignments become significantly more robust when different types of parameters are used together. For example, Yates et al 32 and Gervais et al 30,31 showed that 17 O quadrupole coupling constants could be used in conjunction with 17 O chemical shifts to make unambiguous assignments in cases where overlap of the isotropic shifts made assignment on the basis of shift values alone impossible. The value of NMR-CASTEP in providing results for all nuclides in a system is emphasised by heteronuclear multidimensional experiments.…”
Section: Assignment Of Nmr Signalsmentioning
confidence: 97%